Surfing follicular waves in ovarian stimulation: is there a role for LH in DuoStim protocols? A narrative review and SWOT analysis - Alberto Vaiarelli; Danilo Cimadomo; Maria Cerrillo; Filippo Maria Ubaldi; Juan Antonio García Velasco (Reproductive Biology and Endocrinology)
Abstract IVF treatments should be personalized to collect an appropriate number of oocytes, taking into account the woman’s age and ovarian reserve, in order to maximize the efficacy and efficiency of the IVF process. From a scientific perspective, the ‘continuous recruitment theory’ suggests that several follicular waves are continuously recruited to grow and regress throughout one ovarian cycle. Clinically, this approach has paved the way for the theorization of a double stimulation protocol back-to-back in the same ovarian cycle (DuoStim) to rescue anovulatory waves. This protocol has been successfully adopted by several independent groups in the last decade to improve the number of oocytes in a short timeframe. Although the published data are promising for treating patients of advanced maternal age with reduced ovarian reserve and poor oocyte/embryo competence, the protocols adopted vary across studies. In this challenging population, choosing the appropriate protocol in the DuoStim context is critical to maximize the ovarian response and exploit the potential of individual follicular waves. In this regard, the administration of luteinizing hormone (LH) could be relevant to promote steroidogenesis and folliculogenesis, increase androgen production, improve pre-antral and antral follicle recruitment, and enhance the expression of follicle-stimulating hormone receptors in the granulosa cells. This review presents a step-by-step outline of all DuoStim protocols and proposes a SWOT (strengths, weaknesses, opportunities, threats) analysis of LH administration in the context of DuoStim.